Effects of Carfilzomib Therapy on Left Ventricular Function in Multiple Myeloma Patients - Mingrone, Giulia; Astarita, Anna; Airale, Lorenzo; Maffei, Ilaria; Cesareo, Marco; Crea, Teresa; Bruno, Giulia; Leone, Dario; Avenatti, Eleonora; Catarinella, Cinzia; Salvini, Marco; Cetani, Giusy; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Carfilzomib improves the prognosis of multiple myeloma (MM) patients but significantly increases cardiovascular toxicity. The timing and effect of Carfilzomib therapy on the left ventricular function is still under investigation. We sought to assess the echocardiographic systo-diastolic changes, including global longitudinal strain (GLS), in patients treated with Carfilzomib and to identify predictors of increased risk of cardiovascular adverse events (CVAEs) during therapy. Methods: Eighty-eight patients with MM performed a baseline cardiovascular evaluation comprehensive of transthoracic echocardiogram (TTE) before the start of Carfilzomib therapy and after 6 months. All patients were clinically followed up to early identify the occurrence of CVAEs during the whole therapy duration. Results: After Carfilzomib treatment, mean GLS slightly decreased (−22.2% ± 2.6 vs. −21.3% ± 2.5; p < 0.001). Fifty-eight percent of patients experienced CVAEs during therapy: 71% of them had uncontrolled hypertension, and 29% had major CVAEs or CV events not related to arterial hypertension. GLS variation during therapy was not related to an increased risk of CVAEs; however, patients with baseline GLS ≥ −21% and/or left ventricular ejection fraction (LVEF) ≤ 60% had a greater risk of major CVAEs (OR = 6.2, p = 0.004; OR = 3.7, p = 0.04, respectively). Carfilzomib led to a higher risk of diastolic dysfunction (5.6 vs. 13.4%, p = 0.04) and to a rise in E/e′ ratio (8.9 ± 2.7 vs. 9.7 ± 3.7; p = 0.006). Conclusion: Carfilzomib leads to early LV function impairment early demonstrated by GLS changes and diastolic dysfunction. Baseline echocardiographic parameters, especially GLS and LVEF, might improve cardiovascular risk stratification before treatment.